Is fascia iliaca compartment block administered by paramedics for suspected hip fracture acceptable to patients? A qualitative study - Evans, Bridie Angela (BMJ Open, 2019)
OBJECTIVE: To explore patients’ experience of receiving pain relief injection for suspected hip fracture from paramedics at the location of the injury. DESIGN: Qualitative interviews within a feasibility trial about an alternative to routine prehospital pain management for patients with suspected hip fracture. SETTING: Patients treated by paramedics in the catchment area of one emergency department in South Wales. PARTICIPANTS: Six patients and one carer of a patient who received fascia iliaca compartment block (FICB). INTERVENTION: FICB administered to patients with suspected hip fracture by trained paramedics. We randomly allocated eligible patients to FICB—a local anaesthetic injection directly into the hip region—or usual care—most commonly morphine—using audited scratch cards. OUTCOMES: Acceptability and experience of receiving FICB, assessed through interview data. We audio-recorded, with participants’ consent, and conducted thematic analysis of interview transcripts. The analysis team comprised two researchers, one paramedic and one lay member. RESULTS: Patients had little or no memory of being offered, consenting to or receiving FICB. They recalled the reassuring manner and high quality of care received. They accepted FICB without question. Partial or confused memory characterised experience of subsequent hospital care until surgery. They said their priorities when calling for emergency help were to receive effective care. After hospital treatment, they wanted to regain their health and mobility and resume the quality of life they experienced before their injury. CONCLUSIONS: This study did not raise any concerns about the acceptability of FICB administered at the scene of injury by paramedics to people with suspected hip fracture. It adds to existing evidence about patient and carer experience of on-scene care for people with suspected hip fracture. Further research is needed to assess safety, effectiveness and cost effectiveness of this health technology in a new setting. TRIAL REGISTRATION NUMBER: ISRCTN60065373.